Research Progress of Metal Anticancer Drugs - Yun Bai; Gerile Aodeng; Lu Ga; Wenfeng Hai; Jun Ai (MDPI AG, 2023)
Cancer treatments, including traditional chemotherapy, have failed to cure human malignancies. The main reasons for the failure of these treatments are the inevitable drug resistance and serious side effects. In clinical treatment, only 5 percent of the 50 percent of cancer patients who are able to receive conventional chemotherapy survive. Because of these factors, being able to develop a drug and treatment that can target only cancer cells without affecting normal cells remains a big challenge. Since the special properties of cisplatin in the treatment of malignant tumors were accidentally discovered in the last century, metal anticancer drugs have become a research hotspot. Metal anticancer drugs have unique pharmaceutical properties, such as ruthenium metal drugs with their high selectivity, low toxicity, easy absorption by tumor tissue, excretion, and so on. In recent years, efficient and low-toxicity metal antitumor complexes have been synthesized. In this paper, the scientific literature on platinum (Pt), ruthenium (Ru), iridium (Ir), gold (Au), and other anticancer complexes was reviewed by referring to a large amount of relevant literature at home and abroad.